Prosecuting child soldiers: legal consequences of the participation of children in the Colombian conflict - L. C. Gamarra-Amaya (Law and Safety)
Children have been widely used as pawns in the Colombian armed conflict. International conventions on children’s rights view child soldiers solely as victimized and traumatized; criminalizing the use of children under the age of fifteen in active hostilities. This paper aims to approximate the reality of Colombian child soldiers, versus the approach taken in other jurisdictions, where child soldiers have been the prosecuted in situations of armed conflict.  In making this approximation, we attempt to answer the question of whether it is lawful to prosecute former child soldiers in post-conflict Colombia.